State fragility and development cooperation: Putting the empirics to use in policy and planning - Charles Martin-Shields; Diana Koester (German Institute of Development and Sustainability (IDOS), 2024)
State fragility, which describes how different components of a state do (or do not) function, is a central concept for understanding how development activities and policies in complex political, humanitarian and conflict-affected contexts will (or will not) work in practice. Using fragility as a lens, we use feminist development policy and forced displacement as examples to demonstrate how different empirical conceptualisations of fragility can be used to uncover potential challenges and identify opportunities for more comprehensive policy and programming. These examples are only two ways one can apply the concepts of fragility of the OECD and the German Institute of Development and Sustainability (IDOS). Indeed, these and other empirical concepts of state fragility have many applications and can be used to measure and understand state-society, conflict and humanitarian dynamics in myriad ways. The longest-running among these kinds of models is the Fund for Peace's Fragile States Index (Fund for Peace, 2023). Other models focus on state fragility as a function of different aspects of 'stateness'. This includes IDOS's Constellations of State Fragility typology, which clusters types of fragility based on strengths/weaknesses in key dimensions of statehood (Grävingholt et al., 2019). Some organisations have moved beyond an exclusive focus on the functioning of the state, with the OECD currently defining fragility contexts as the combination of risks and insufficient coping capacities of multiple levels of governance systems and/or communities to manage, absorb or mitigate those risks (OECD, 2016). The IDOS and OECD concepts do not rank countries, and the methods used in both models allow them to be applied to different levels of analysis. Essentially, these empirical conceptualisations of state fragility can serve as useful heuristics for the policy-makers responsible for setting policy agendas in fragile contexts. The key challenge for policy-makers that we address in this policy brief is the step from empirically categorising states' fragility, to using that empirical data to inform often fast-moving, idiosyncratic policy-making and implementation in fragile contexts. As noted previously, these concepts are heuristics; country-specific policy planning and implementation require more fine-grained monitoring of country contexts. To achieve this, we recommend: Donors should be aware that the suitability of a particular tool/ fragility lens depends on the specific problem at hand, and they should choose the tool following a rigorous problem analysis. Use Germany's leadership on feminist foreign and development policy to capture and highlight the full range of links between gender and fragility, and to continue strengthening feminist foreign and development policy in fragile contexts. In many cases, state fragility is a neighbourhood challenge that requires regional coordination in order to be managed. In the case of migration and displacement, donors can support the freedom of movement protocols in regional agreements such as ECOWAS and the Intergovernmental Authority on Development (IGAD). Policy-makers and donor organisations should deepen investment in new avenues for collecting and standardising the data that is used to generate different empirical concepts of state fragility. This includes funding on-the-ground monitoring activities such as IGAD's Conflict Early Warning and Response Mechanism in East Africa. Recognise that otherwise functional states can indeed have sub-national pockets of severe fragility, and that these variations in sub-national fragility can over time erode the capacity, legitimacy and authority of the state if left unchecked.
Keywords: 320